PENGARUH KEPUASAN KERJA, PERSEPSI DUKUNGAN ORGANISASI DAN KEPEMIMPINAN SPIRITUAL TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR PADA PT MNC SKY VISION TBK - Quisty Arinnandya; La Diadhan Hukama (Universitas Putera Batam, 2018)
The purpose of this study were 1) to analyze the influence of job satisfaction on organizational citizenship behavior. 2) To analyze the influence of perceived organizational support on organizational citizenship behavior. 3) To analyze the the influence of spiritual leadership on organizational citizenship behavior. The population in this study were employees of PT MNC Sky Vision TBK, with the number of 40 people. Data analysis used are validity, reliability testing, regression, t test and the coefficient of determination. The results of the study showed that: (1) job satisfaction has positive and significant effects on organizational citizenship behavior (2) perceived organizational support has positive and significant effects to organizational citizenship behavior (3) spiritual leadership has positive and significant effects on organizational citizenship behavior (4) simultaneously all variables are affecting organizational citizenship behavior positively and significantly.